The Nature of God's Existence as Understood by the Bible and the Qur'an - Opeloye, Muhib O. (2014)
The Biblical teachings on the nature of God appear somewhat equivocal as the Old Testament's and the New Testament's views on this subject are diametrically opposed. While the former tends to affirm God's corporal existence as evident in the instances where Biblical figures are reported to have seen God, and passages ascribing parts of human body or human emotions to Him, the latter on the other hand asserts that God is spirit and consequently cannot be seen. This seeming irreconcilable position led to theological argumentation about the nature of God between the Christian anthropomorphists and the spiritualists.